MODERASI BERAGAMA SEBAGAI SOLUSI DALAM MEMBENDUNG BAHAYA ISLAMOPHOBIA UNTUK MENJAGA KEHARMONISAN NEGARA KESATUAN REPUBLIK INDONESIA - Sarina Aini (SYARIAH: Journal of Islamic Law, 2021)
Religious moderation is an effort to preserve traditions and foster friendly religious ideas. In other words, the idea of religious moderation is actually an option to preserve Indonesia's diversity without having to uproot existing traditions and cultures. In the case of Islamophobia, it is necessary to change a person's mindset or mindset so that there is no bad prejudice against other religions. It is undeniable that Islamophobia can make people devoid of morals or become immoral. Because he makes excessive fear so that negative views arise against fellow Muslims. To stop the spread of Islamophobia, it is necessary to apply the concept of religious moderation in order to maintain the harmony of the Unitary State of the Republic of Indonesia. This can be done in theological, political, sociological, and judicial frameworks. This harmony between the people and the Indonesian state is guided by the agreement, Pancasila, the 1945 Constitution, Bhineka Tunggal Ika, and the unitary state of the Republic of Indonesia (four pillars), which must be upheld as supporters. As a diverse country, what we really want is to live in harmony in a diverse atmosphere, but this is not just a dream for each of us to participate. Of course, differences must be positioned as assets to build harmony itself.